Gliomas and the vascular fragility of the blood brain barrier - Dubois, Luiz Gustavo; Campanati, Loraine; Righy, Cassia; D’Andrea-Meira, Isabella; Spohr, Tania Cristina Leite de Sampaio e; Porto-Carreiro, Isabel; Pereira, Claudia Maria; Balça-Silva, Joana; Kahn, Suzana Assad; DosSantos, Marcos F.; Oliveira, Marcela de Almeida Rabello; Ximenes-da-Silva, Adriana; et al. (Frontiers in Cellular Neuroscience, 2014)
Astrocytes, members of the glial family, interact through the exchange of soluble factors or by directly contacting neurons and other brain cells, such as microglia and endothelial cells. Astrocytic projections interact with vessels and act as additional elements of the Blood Brain Barrier (BBB). By mechanisms not fully understood, astrocytes can undergo oncogenic transformation and give rise to gliomas. The tumors take advantage of the BBB to ensure survival and continuous growth. A glioma can develop into a very aggressive tumor, the glioblastoma (GBM), characterized by a highly heterogeneous cell population (including tumor stem cells), extensive proliferation and migration. Nevertheless, gliomas can also give rise to slow growing tumors and in both cases, the afflux of blood, via BBB is crucial. Glioma cells migrate to different regions of the brain guided by the extension of blood vessels, colonizing the healthy adjacent tissue. In the clinical context, GBM can lead to tumor-derived seizures, which represent a challenge to patients and clinicians, since drugs used for its treatment must be able to cross the BBB. Uncontrolled and fast growth also leads to the disruption of the chimeric and fragile vessels in the tumor mass resulting in peritumoral edema. Although hormonal therapy is currently used to control the edema, it is not always efficient. In this review we comment the points cited above, considering the importance of the blood brain barrier and the concerns that arise when this barrier is affected.